Emotion mapping: Using participatory media to support young people's participation in urban design. (August 2018) - Deitz, Milissa; Notley, Tanya; Catanzaro, Michelle; Third, Amanda; Sandbach, Katrina
Abstract: Young people's participation in urban design is usually either highly restricted or excluded altogether. This paper reflects on a pilot project that explored how communication technologies can be used to support young people to shape the development of their city. A research team at Western Sydney University developed an emotion-mapping platform (invisiblecity.org.au) and offered creative media workshops to young people in Western Sydney's City of Parramatta to support them to explore different ways of expressing emotion through text and image. The study found that emotion mapping provides opportunities to open up discussions about affective experiences of the city that can be integrated into urban planning. However, we argue that such initiatives must overcome the challenges associated with tapping into, making sense of, and amplifying complex, dispersed and always changing everyday media practices if they are to be embraced by young people in ways that ensure they are inclusive and representative. Further, it is critical that initiatives work out how to encourage urban developers to hear and value young people's perspectives on urban environments and how they use them.